2020
DOI: 10.1007/s10336-020-01744-1
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of plumage coloration and genetic variation confirm the hybridization of Pipra fasciicauda and Pipra aureola in the Brazilian Amazon basin

Abstract: We thank the curators and curatorial assistants of the Goeldi Museum in Belém and the National Institute for Amazonian Research (INPA) in Manaus for allowing us to obtain tissue samples from the specimens under their care. AA is supported by a CNPq research productivity fellowship, #306843/2016-1. PVC is supported by a CAPES (the Brazilian Higher Education Training Program) doctoral fellowship, #1537057.We also thank CAPES for financial support throughout this study, the UFPA Institute of Coastal Studies and G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…In addition to these hybrid zones for six pairs of parapatric taxa, two additional parapatric pairs occur for which we lacked sufficient geographical sampling to assess hybridization. P. a. aureola and P. f. scarlatina are documented to hybridize (Sampaio et al, 2020). We detected no admixture in the nearest sampled populations of P. f. scarlatina (located along the lower Xingu River located just 150 km south of the Amazon River where P. a. aureola occurs), but small traces of P. f. scarlatina ancestry (up to 4%) were reconstructed to occur in geographically adjacent populations of P. a. aureola (population 5, Figure 1f) from north of the Amazon River, but not in distant populations (population 3 , Figure 1f), suggesting a hybrid zone probably occurs in the unsampled region.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these hybrid zones for six pairs of parapatric taxa, two additional parapatric pairs occur for which we lacked sufficient geographical sampling to assess hybridization. P. a. aureola and P. f. scarlatina are documented to hybridize (Sampaio et al, 2020). We detected no admixture in the nearest sampled populations of P. f. scarlatina (located along the lower Xingu River located just 150 km south of the Amazon River where P. a. aureola occurs), but small traces of P. f. scarlatina ancestry (up to 4%) were reconstructed to occur in geographically adjacent populations of P. a. aureola (population 5, Figure 1f) from north of the Amazon River, but not in distant populations (population 3 , Figure 1f), suggesting a hybrid zone probably occurs in the unsampled region.…”
Section: Resultsmentioning
confidence: 99%
“…While subspecies have been defined within each species, previous authors have noted extensive individual variation within populations in the plumage characters used to delimit subspecies, and have suggested that some subspecies may not be valid (Kirwan & Green, 2011;Snow, 2004). Hybrids have been reported along contact zones between each of these species pairs (Haffer, 1997;McCarthy, 2006;Sampaio et al, 2020), but the extent of hybridization is unknown. eages into reproductively isolated species.…”
Section: Introductionmentioning
confidence: 99%